Spectroscopic study of solvent effects on the electronic absorption spectra of morpholine and its complexes - Masoud, Mamdouh Saad; Ali, Alaa Eldin; Elasala, Gehan Shaaban; Elwardany, Rehab Elsaid (European Journal of Chemistry, 2023)
The electronic absorption spectra of morpholine and its five morpholine complexes have been studied in different solvents of various polarities. The regression and correlation coefficients have been calculated with the SPSS program. Solvation energy relationships were deduced from spectral shifts and correlated with solvent parameters α (solvent hydrogen bond donor acidity), β (solvent hydrogen bond acceptor basicity), and π* (dipolarity/polarizability). The percentage contributions of the calculated solvatochromic parameters show that classic solvation effects play a major role in explaining the spectral shifts in all investigated complexes. The blue shift of [Fe(MOR)3Cl3]·4H2O, [Ni(MOR)4Cl2]·4H2O, and [Cu(MOR)4Cl2]·6H2O complexes is due to the formation of hydrogen bonds, which suggests the stabilization of the ground electronic state compared with the excited state. [CuNi(MOR)2Cl4]·4H2O and [CuZn(MOR)3Cl4]·2H2O are mixed metal complexes that suffer a red shift due to the solute-solvent interactions, which causes stabilization of the excited solute state with increasing solvent polarity. The bands are affected by specific solute-solvent interactions including hydrogen bond donor ability (acidity) and hydrogen bond acceptor ability (basicity) and nonspecific solute-solvent interactions including electromagnetic interaction between the dipole moments of solute and polar solvents.